1994
DOI: 10.1111/j.1532-5415.1994.tb06543.x
|View full text |Cite
|
Sign up to set email alerts
|

Physician Staffing Patterns Correlates of Nursing Home Care: An Initial Inquiry and Consideration of Policy Implications

Abstract: Medical organization and practice patterns emerge as important factors in considerations of nursing home quality. Results argue that, as in acute settings, limiting practice privileges in nursing homes may be a useful organizational strategy to improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 13 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Support for a structured model can be found in the work of Roemer and Friedman (23) and others (24–26) who have shown an association between structured medical staff and quality of care. In our own work, which examines the impact of medical staff organization in nursing homes, physicians working within a closed staff model seemed to be more committed, knowledgeable about long-term care practice, and available (20). Existing policies, regulations, and care standards that define the role of the attending physician and medical director in the nursing home reinforce such a model (27, 28), as do programs for formal certification of medical directors (29).…”
Section: A Possible Solutionmentioning
confidence: 99%
“…Support for a structured model can be found in the work of Roemer and Friedman (23) and others (24–26) who have shown an association between structured medical staff and quality of care. In our own work, which examines the impact of medical staff organization in nursing homes, physicians working within a closed staff model seemed to be more committed, knowledgeable about long-term care practice, and available (20). Existing policies, regulations, and care standards that define the role of the attending physician and medical director in the nursing home reinforce such a model (27, 28), as do programs for formal certification of medical directors (29).…”
Section: A Possible Solutionmentioning
confidence: 99%
“…It is also possible that only a small fraction of residents received their care from those physicians that were retained by employment arrangements, therefore it was important to include a measure of the degree to which residents received care from non-employed physicians. This latter measure had been used before to capture the related concept of open/closed practice staff model 2, 13,14 . Credentialing is another way a NH can control its physician resources.…”
Section: Introductionmentioning
confidence: 99%
“…Available research also points to better delivery of quality care for facilities that use the "closed" physician staffing models (only select, credentialed physicians can provide clinical care in the facility). 9 In the same context, research has shown that higher performance on certifications in internal medicine (IM) and family practice (FP) specialties lead to better utilization and patient outcomes. 10,11 This is relevant as IM and FP specialists most commonly serve as NH medical directors.…”
mentioning
confidence: 99%